Refractory Anaemia with Hyperoxalurea - Ehsan Ayesha; Lone Ayaz; Sabir Omer; Tareef Nauman; Riaz Sabiha; Tanvir Imrana (Journal of Nephrology Advances, 2015)
We report 2 cases of primary hyperoxalurea who presented with refractory anaemia, nephrolithiasis, renal failure warranting repeated renal transplantation in one of the cases. Renal biopsy of the patients revealed crystals of calcium oxalate in the tubules. The same crystals were also visualized in bone marrow biopsy which confirmed the diagnosis of systemic oxalosis. We conclude that Primary hyperoxalurea may rarely cause anemia secondary to calcium oxalate crystal deposition in the bone marrow.
Keywords: primary hyperoxalurea